Penerapan Error Correction Mechanism Pada Determinan Volume Ekspor Minyak Kelapa Sawit Indonesia Periode 2016-2019 - Aldi Firmansyah; Milan Puji Astuti (Seminar Nasional Official Statistics, 2022)
Palm oil is one of Indonesia's leading export commodities. The important role of palm oil exports is one of the backgrounds in this research. The purpose of this study is to determine the determinants or factors that affect the volume of palm oil exports in Indonesia in the period 2016 to 2019. The method used in this study is descriptive analysis and inferential analysis using the Error Correction Mechanism (ECM) approach model. The results showed that all research variables were cointegrated with each other. Then in the short term and long term with a significance level of 10 percent, only the rupiah exchange rate against the US$ variable significantly affects the volume of Indonesian palm oil exports.